Cross-Cultural Validation of the Inventory of School Motivation (ISM) in the Asian Setting: Hong Kong and the Philippines - King, Ronnel B. (Springer Netherlands, 2011)
Students’ achievement goals in school have received increasing research attention because they have been shown to be important in predicting important outcomes. As such, there has been a growing interest in measuring and comparing them across different cultural groups. However, these comparisons cannot be made until validity evidence has been attained to support the use of an instrument in the new cultural setting. In this study, we investigated the cross-cultural applicability of the Inventory of School Motivation (ISM, McInerney et al. American Educational Research Journal 34:207-236, 1997) in the Hong Kong Chinese and Philippine contexts using both within-network and between-network approaches to construct validation. The ISM measures four types of achievement goals: mastery, performance, social, and extrinsic goals. 1,406 high school students from Hong Kong (n = 697) and the Philippines (n = 709) participated. Results of the within-network test showed that the ISM had good internal consistency reliability and the confirmatory factor analysis provided support for the hypothesized four-factor model. Multigroup confirmatory factor analyses supported invariance of factor loadings across the two samples. The between-network test also indicated that these achievement goals correlated systematically with different aspects of students’ self-concepts. These findings support the applicability of the ISM among Hong Kong Chinese and Filipino students.